Diagnostic and prognostic utility of salivary and serum procalcitonin, interleukin-6, and interleukin-10 in pediatric pneumonia: a prospective case-control study - Rezk, Ahmed; Bakry, Nehad; Elfiky, Samar; Metawaa, Maha; Ibrahim, Ahmed (Frontiers in Pediatrics, 2025)
ObjectivesEffective biomarkers are essential for improving the diagnosis and risk stratification of pediatric pneumonia. This study aimed to evaluate the diagnostic and prognostic utility of salivary and serum interleukin (IL)-6, interleukin (IL)-10, and procalcitonin (PCT) in children diagnosed with pneumonia.MethodsA prospective case-control study was conducted involving 50 children under five years of age with community-acquired pneumonia (CAP) and 50 age- and sex-matched healthy controls. At admission, serum and saliva samples were collected, and levels of PCT, IL-6, and IL-10 were measured using ELISA. Receiver operating characteristic (ROC) curve analysis was used to evaluate the diagnostic performance of each biomarker in distinguishing children with pneumonia from healthy controls. Multivariate logistic regression was then applied to identify independent predictors of disease severity.ResultsAll three biomarkers demonstrated exceptional diagnostic accuracy in distinguishing pneumonia from healthy controls. Salivary PCT (>68.5 pg/ml, AUC = 1.000) and serum IL-10 (>73.18 pg/ml, AUC = 1.000) achieved perfect diagnostic performance with 100% sensitivity and 100% specificity. Serum IL-6 (>18.06 ng/L, AUC = 0.994) and serum PCT (>86.66 pg/ml, AUC = 0.962) also demonstrated excellent accuracy with 96% sensitivity and 100% specificity. The neutrophil-to-lymphocyte ratio (>0.8, AUC = 1.000) similarly achieved 100% sensitivity and specificity. Severe pneumonia was associated with higher IL-10 and PCT levels (both serum and saliva), younger age, elevated heart rate, and higher CRP. IL-6 did not correlate with severity. In multivariate analysis, age <6 months (OR: 3.85), neutrophil-to-lymphocyte ratio (OR: 3.40), serum IL-10 (OR: 5.75), and salivary PCT (OR: 4.25) independently predicted severe pneumonia.ConclusionsSalivary and serum IL-6, IL-10, and PCT show promising diagnostic potential for pediatric pneumonia when compared to healthy controls. IL-10 and PCT also demonstrate prognostic value for severity stratification, with salivary measurements closely mirroring serum results. While these findings suggest potential for saliva-based diagnostics as non-invasive tools for early detection and severity assessment in pediatric pneumonia, validation in clinical settings with symptomatic controls is needed to establish their practical diagnostic utility in differentiating pneumonia from other febrile illnesses.